Representações sociais de aborto para ginecologistas e obstetras da Região Metropolitana de Belo Horizonte/MG - Thiago Mikael Silva (2020)
Nowadays, unsafe abortion represents a relevant public health issue, principally in developing countries, where legislation tend to be more restrictive. In Brazil, prevails the 1940s Criminal Code, which in conjunction with specific jurisprudence, exclusively allow abortion carried out by physicians in cases of pregnant woman life risk, pregnancy resulting from rape and anencephaly. Since criminalization does not prevent clandestine abortion practice, on the one hand, a great parcel of women practice unsafe abortion. And it is not uncommon the later need to seek health services to treat possible complications. On the other hand, part of female public seeks legal abortion services to exercise this right. Besides the low coverage of this sort of service, women health assistance is frequently passed through institutional violence. As well as, judgment, discrimination, mistreatment and other improper practices committed by healthcare teams. Specially among gynecologists/obstetricians, the fear of suffering discrimination from their equals and their personal conceptions of abortion make many ones refuse carrying out this procedure. It includes one more obstacle in guaranteeing women's rights. Supported by Qualitative Research and based on Social Representations Theory procedural approach's assumptions, this study aimed to identify and analyze gynecologists and obstetricians' Social Representations of abortion. Twenty physicians who act or acted in maternity centers, gynecology/obstetrics ambulatories and hospitals in Belo Horizonte Metropolitan Area were interviewed. The interviews aimed to explore these professionals' experience, their perceptions, practices and social representations of abortion, besides the way these individuals elaborate such representations. The interviews were recorded, transcribed and analyzed through Content Analysis. Results point abortion is recurrent in the interviewed professionals' daily routine. It mobilizes them to share social representations that help abortion become a familiar object from basic values and from references close to groups which polarize abortion debate. However, this process does not happen without significant conflicts and contradictions, characterizing representations identified as the polemic social ones. For the majority of the participants, abortion was objectified as Decision/Right, anchored in basic values such as liberty that may lead to women autonomy defense, acceptance, abortion practice in legal conditions and abortion legalization support in Brazil. Through abortion practice, physicians believed they were helping women, minimizing their suffering. In parallel, other parcel of participants presented a different understanding. To these professionals, abortion was objectified as Murder. Its anchorage happened through basic values one considers unquestionable such as life, what may lead to fetus defense, disapproval, discomfort and conscientious objection to abortion even when it is foreseen by Brazilian Law. Some professionals believed abortion would be the fetus murder and an aggression to female body, generating marks and traumas in patients. Therefore, interviewees' social representations comply relevant roles in their daily routine and generates convergence points to their practices. Nevertheless, there were conflicting issues between their personal views and professional practices. It points to the need of further studies which explore this dimension in the light of cognitive polyphasia.